2017
DOI: 10.1039/c6cp08756f
|View full text |Cite
|
Sign up to set email alerts
|

Spin relaxation studies of Li+ ion dynamics in polymer gel electrolytes

Abstract: Two ternary polymer gel electrolyte systems are compared, containing either polyethylene oxide (PEO) or the poly-ionic liquid poly(diallyldimethylammonium) bis(trifluoromethyl sulfonyl)imide (PDADMA-TFSI). Both gel types are based on the ionic liquid 1-butyl-1-methylpyrrolidinium bis(trifluoromethyl sulfonyl)imide (PTFSI) and LiTFSI. We study the influence of the polymers on the local lithium ion dynamics at different polymer concentrations using Li spin-lattice relaxation data in dependence on frequency and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 41 publications
6
16
0
Order By: Relevance
“…In spite of the lower local activation energy, the correlation times are higher for the PIL2–4 ter systems. However, such an opposing trend of correlation time and activation energy is in accordance with previous results for PIL1 …”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…In spite of the lower local activation energy, the correlation times are higher for the PIL2–4 ter systems. However, such an opposing trend of correlation time and activation energy is in accordance with previous results for PIL1 …”
Section: Resultssupporting
confidence: 93%
“…A strategy to hinder this migration toward the anode is to break the lithium anion cluster. In recent studies, we have shown that these clusters are partially suppressed if the cationic polymer PDADMA + , corresponding to PIL1 in the present study, is used. , …”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…[ 10 ] It was shown that the specific interactions of the functional polymer groups with the ionic constituents can significantly alter ion transport. [ 9b,11 ]…”
Section: Introductionmentioning
confidence: 99%
“…Regarding their applications in industry, ILs have gained special interest because they are considered as alternative solvents in many applications because of their unique properties such as nonflammability, negligible vapor pressure, and exceptional chemical and thermal stability . These properties make ILs very attractive materials to be used as dye‐sensitized solar cells, green solvents with low environmental impact, the design of IL crystals, and part of electrolytes in lithium‐ion batteries, among many other applications …”
Section: Introductionmentioning
confidence: 99%